Investigating the Effect of Pouring Temperature Variations on Casting Defects of Making Camshaft Covers for Yamaha Jupiter Motorcycles Using Sand Casting Method - Asril l. Fabanyo,; Ivan Junaidy A. Karim,; Bambang Tjiroso, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Casting using the sand-casting method is one of several methods in the metal casting process. The pouring temperature in the casting process is critical because it affects the casting results. This study aims to determine the effect of variations in pouring temperature on porosity defects in used aluminum metal castings and the impact of variations in pouring temperature on casting defects. The aluminum is melted and poured into the molds used are clay molds; In general, the mold is divided into two parts, namely the top (cup) and the bottom (drag), so that after the mold is finished, the melted aluminum is poured into the mold with variations in pouring temperature of 660˚C, 690C, and 720˚C. The method used is the observation method which is done by direct observation of the object of research. From the analysis of porosity defects data, the higher the casting temperature, the lower the porosity defects; a temperature of 660 C with a percentage value of 36.8%, a temperature of 690 C with a percentage value of 34.8%, and a temperature of 720˚C with a percentage value of 34.5%. This shows that casting temperature affects casting defects and porosity.